2010
DOI: 10.1111/j.1538-7836.2009.03733.x
|View full text |Cite
|
Sign up to set email alerts
|

Which platelet function test is suitable to monitor clopidogrel responsiveness? A pharmacokinetic analysis on the active metabolite of clopidogrel

Abstract: is suitable to monitor clopidogrel responsiveness? A pharmacokinetic analysis on the active metabolite of clopidogrel. J Thromb Haemost 2010; 8: 482-8.Summary. Background: Multiple platelet function tests claim to be P2Y12-pathway specific and capable of capturing the biological activity of clopidogrel. Objectives: The aim of the present study was to determine which platelet function test provides the best reflection of the in vivo plasma levels of the active metabolite of clopidogrel (AMC). Patients/methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 27 publications
4
69
1
Order By: Relevance
“…A strong agreement between aggregation measurements with Verify Now and VASP-test could also be shown by Bidget et al (5). VASP-test and Verify Now also showed the best correlation with the plasma concentration of active Clopidogrel metabolites, so that these two tests were particularly recommended for monitoring Clopidogrelinduced platelet inhibition (10). The VASP test has a very high prognostic value for ischemic events in patients undergoing treatment with P2Y 12 -receptor antagonists following PCI (26).…”
Section: Introductionmentioning
confidence: 70%
“…A strong agreement between aggregation measurements with Verify Now and VASP-test could also be shown by Bidget et al (5). VASP-test and Verify Now also showed the best correlation with the plasma concentration of active Clopidogrel metabolites, so that these two tests were particularly recommended for monitoring Clopidogrelinduced platelet inhibition (10). The VASP test has a very high prognostic value for ischemic events in patients undergoing treatment with P2Y 12 -receptor antagonists following PCI (26).…”
Section: Introductionmentioning
confidence: 70%
“…A previous study showed that LTA, the VASP index, and the VerifyNow-P2Y12 assay were correlated with the in vitro plasma levels of the active metabolite of clopidogrel. 29) Routine monitoring of PRU immediately after TAVI could predict future bleeding events, allowing adjustment of the clopidogrel dose.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in our study, patients on adjunctive therapy with GP IIb/IIIa inhibitors when compared with those receiving exclusively aspirin and clopidogrel were numerically more likely to present with HTPR at baseline according to the VASP assay. Not only does the VASP assay facilitate the risk stratification process in ACS patients undergoing PCI [10][11][12][13][14], but according to a recent study, it also provides the best reflection of the in vivo plasma level of the active metabolite of clopidogrel when compared with light transmission aggregometry, Verify-Now ® system, whole blood aggregometry, and the IMPACT-R ADP test [25]. Numerous pharmacodynamic studies including unselected patients in terms of their baseline platelet reactivity demonstrated that prasugrel much stronger than clopidogrel, even with high doses of the latter (i.e.…”
Section: Discussionmentioning
confidence: 99%